The effect of plastic deformation on hydrogen diffusion in nickel Alloy 625. (15th March 2023) - Lu, Xu; Díaz, Andrés; Ma, Jun; Wang, Dong; He, Jianying; Zhang, Zhiliang; Johnsen, Roy
Abstract: Recently, several hydrogen-assisted failures have been reported on different nickel alloys used in the subsea oil and gas industries. It is thus essential to correlate hydrogen uptake and diffusion behavior with stress conditions for an in-depth understanding of the failures. This study reports the first-hand finding on hydrogen diffusion behavior in a nickel Alloy 625 under different pre-strain levels by combining the electrochemical permeation test and diffusion model, with a particular focus on the effect of grain boundary carbide. As the multiplication of dislocations was claimed to trap hydrogen atoms and reduce the diffusivity by increasing the strain levels from 0.05 to 0.2, an acceleration in hydrogen diffusivity was however observed when the strain was higher than 0.1. This phenomenon was deduced to be caused by the diffusion highways by the hydrogen-enhanced strain-induced vacancy formation at the grain boundaries and reduced hydrogen trapping by the fractured carbides. Graphical abstract: Image, graphical abstract